Therapeutic drug monitoring of colistin in patients with carbapenem-resistant infections and varying renal function: a series case report of 5 patients - Qiuyu Zhu; Juan Wang; Fangqiong Li; Ji Shen; Xiaoting Gong; Bo Yang; Xufen Xia; Yuexing Tu (Medicine, 2026)
Rationale: Carbapenem-resistant gram-negative bacterial infections remain a challenge. Colistin is an important treatment option but exhibits substantial pharmacokinetic variability and nephrotoxicity, particularly in critically ill patients with altered renal function. Patient concerns: Five critically ill patients (aged from 25 to 94) with infections in the setting of heterogeneous underlying conditions, including hematologic malignancy, acute respiratory failure, severe trauma, chronic obstructive pulmonary disease, and acute cerebral infarction. Their renal function varied markedly, ranging from augmented renal clearance to severe renal impairment. Diagnoses: Carbapenem-resistant Klebsiella pneumoniae , carbapenem-resistant Acinetobacter baumannii , or both were identified during hospitalization. The patients exhibited different renal function profiles. Acute kidney injury was observed in cases 2 to 5, and cases 3 to 5 required continuous renal replacement therapy. Interventions: All patients received intravenous colistin sulfomethate sodium, with plasma colistin concentrations quantified by liquid chromatography–triple quadrupole mass spectrometry; dosing was adjusted according to clinical course and renal function. Outcomes: Colistin plasma concentrations varied considerably among patients and were not simply inversely related to renal function. All patients achieved the ratio of the unbound area under the concentration–time curve to the minimum inhibitory concentration target for systemic infection, and 3 additionally achieved the higher target for pulmonary infection; however, a favorable clinical outcome was observed in only 2 of the 5 cases. Lessons: Colistin exposure cannot be predicted only from renal function; therapeutic drug monitoring may assist in individualized colistin sulfomethate sodium dosing, particularly in patients with augmented renal clearance or markedly altered renal function. Moreover, the target of unbound area under the concentration–time curve to the minimum inhibitory concentration attainment does not necessarily translate into clinical success, indicating that clinical efficacy is also influenced by disease severity and patient-specific factors.